Providing psychiatric diagnosis and intervention in patients with chronic medical illness in the community: A novel collaboration between the Psychiatry team and the community team in a Singapore restructured hospital - W. S. Lee; G. S. Lim; H. Y. Goh; Y. S. Chan (European Psychiatry, 2024)
Introduction Home nursing and medical services have an established role in delivering chronic medical care to populations which face difficulty accessing physical clinics. Those with chronic medical conditions and reduced mobility face a higher likelihood of suffering from psychiatric co-morbidity. However, till date there has been limited research done on home-based psychiatric care in this population. Since 2021, the Psychiatry department of Tan Tock Seng Hospital (TTSH) has been collaborating with TTSH Community Health Team (CHT) to manage potential psychiatric issues in community patients. These patients would be discussed in a weekly multidisciplinary setting. If indicated, home visit by both teams for home-based assessment and treatment would be arranged, allowing for detection and treatment of psychiatric illness.